Genre Variations Of Orazbay Abdirakhmanov`S Publication «Teńiz Toli, Ay Jariq» - Aqsıngúl Aymuratova (Zien Journals, 2024)
This article analyzes the genre characteristics of O. Abdurakhmanov's work "The Sea is Full, the Moon is Bright". Information is given about the origin of this genre and what works were created in the literary field.
Keywords: Genre; fantasy; fiction; motif